AUSTRIAN MANAGEMENT - Asadov, Nurislom (Science technology&Digital finance, 2023)
The history of Austrian management is deeply connected with the rich cultural and economic heritage of the country. Austria has a long history of entrepreneurship and innovation, characterized by a unique combination of traditional values and modern management practices. In Austrian governance, decisions are often made through consensus and consultation. Managers typically involve key stakeholders in the decision-making process to ensure collective bargaining before moving forward.